2016
DOI: 10.1017/s1049096516001487
|View full text |Cite
|
Sign up to set email alerts
|

The Growing Spatial Polarization of Presidential Voting in the United States, 1992–2012: Myth or Reality?

Abstract: There has been considerable debate regarding a hypothesis that the American electorate has become spatially more polarized over recent decades. Using a new method for measuring polarization, this paper evaluates that hypothesis regarding voting for the Democratic party's presidential candidates at six elections since 1992, at three separate spatial scales. The fi ndings are unambiguous: polarization has increased substantially across the country's nine census divisions, across the 49 states within those divisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…In a result that is closely related to our analysis, Charyyev and Gunes (2019) [14] find that county-level migration flows in the U.S. point more heavily to Republican and politically moderate counties. The literature also indicates that counties and other geographic areas are becoming more polarized along party voting lines—a dynamic that is related to county in- and out-migration rates [15, 16]. In summary, the existing research has demonstrated a general tendency for individuals to prefer living among co-partisans, and that local areas have grown more partisan in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…In a result that is closely related to our analysis, Charyyev and Gunes (2019) [14] find that county-level migration flows in the U.S. point more heavily to Republican and politically moderate counties. The literature also indicates that counties and other geographic areas are becoming more polarized along party voting lines—a dynamic that is related to county in- and out-migration rates [15, 16]. In summary, the existing research has demonstrated a general tendency for individuals to prefer living among co-partisans, and that local areas have grown more partisan in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…Morrill was engaged as a population geographer by a court to redraw the electoral district of Washington State in the 1970s(Morrill, 1973) and wrote further about the issue(Morrill, 1981) but not about challenging gerrymanders. 7 I should note that our work on multilevel modelling of the spatial polarization of the US electorate appeared too late for Hopkins to notice it(Johnston et al, 2016a(Johnston et al, , 2016bRohla et al, 2018).…”
mentioning
confidence: 99%
“…In recent years, the partisan and ideological divide between urban and rural areas has become increasingly visible (Brownstein 2016;Cramer 2016;Johnston et al 2016;Sussell 2013;Walsh 2012). Throughout the nation there are increasingly one-sided voting patterns at many locations, and a steady erosion in the number of voters living in politically competitive settings (Bishop 2009;Johnston et al 2016). Psychologists propose that the formation of geographic pockets of sociopolitical similarity are a response to the psychological need for belonging (Golman et al 2016;Sirgy et al 2005).…”
mentioning
confidence: 99%